Endless Digging and Endless Picking. Sex Ratios and Gendered Labour in Surinamese Plantations, 1830–1863 - Cornelis W. van Galen; Björn Quanjer; Matthias Rosenbaum-Feldbrügge; Matthijs Kraijo (Historical Life Course Studies)
In this article we study the question why the sex ratio among the enslaved population of plantation workers reversed from a male to a female surplus between 1830 and the abolition of slavery in 1863. We use the Historical Database of Suriname (HDS) to answer this question in three steps. First, we give a broad overview of the changing sex ratios in the various Surinamese regions between 1838 and 1861. Second, we study the age structure on three plantations in the district Coronie in 1830 in detail. Finally, we use muster rolls available for the Catharina Sophia plantation in the period 1848–1849 to analyse the gendered division of labour. Our results indicate that both the male surpluses during the 1830s and the subsequent skew of the sex ratios towards females were the effects of a gendered division of labour, in which plantation managers preferred male labourers for heavy and unhealthy work in the construction and upkeep of plantation polders. This led to an excess mortality of enslaved men.